2021
DOI: 10.1016/j.earlhumdev.2020.105272
|View full text |Cite
|
Sign up to set email alerts
|

No credible evidence for links between 2D:4D and COVID-19 outcomes: A probabilistic perspective on digit ratio, ACE variants, and national case fatalities

Abstract: Research into COVID-19 susceptibility and outcomes are critical, but claims must be carefully evaluated to inform policy decisions. In a recent series of articles, Manning and Fink [1–3] use national-level data to describe associations between case-fatality ratios and male and female finger ratios (2D:4D), a suggested measure of prenatal androgen exposure, as well as angiotensin-converting enzyme (ACE) allele and genotype frequencies. The authors suggest that 2D:4D is linked with ACE variant prevalence, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…There is considerable support for the link between 2D:4D and prenatal sex steroids 13 but for a contrasting view see McCormick & Carre, 2020 14 . Manning and Fink found that nations with high CFR’s had high mean male 2D:4D 9 , thus supporting the hypogonadal theory (in support see Sahin, 2020 and for a critical view see Jones et al, 2020 15 , 16 ). With regard to right–left asymmetry of 2D:4D, i.e.…”
Section: Introductionmentioning
confidence: 90%
“…There is considerable support for the link between 2D:4D and prenatal sex steroids 13 but for a contrasting view see McCormick & Carre, 2020 14 . Manning and Fink found that nations with high CFR’s had high mean male 2D:4D 9 , thus supporting the hypogonadal theory (in support see Sahin, 2020 and for a critical view see Jones et al, 2020 15 , 16 ). With regard to right–left asymmetry of 2D:4D, i.e.…”
Section: Introductionmentioning
confidence: 90%
“…These variations in androgen levels have been seen in the patients treated with ADT in prostate cancer treatment [ 112 , 113 , 119 , 120 ]. According to statistics from around the world, males are more likely to contract SARS-CoV-2 coronavirus infections than females.…”
Section: Sars-cov-2 Infection and Male Infertilitymentioning
confidence: 99%
“…AGA is caused due to the higher androgen levels in the hair follicles as it results in the formation of dihydrotestosterone. In young individuals, severe steroid intake causes hyperandrogenization [ 119 , 124 ]. Adrenal androgens have not yet been considered when studying how androgens affect SARS-CoV-2 infections because they make up a small portion of all androgens and can change throughout the illness, particularly when dexamethasone is administered [ 125 ].…”
Section: Sars-cov-2 Infection and Male Infertilitymentioning
confidence: 99%